Hormonal replacement therapy and obesity - Paszkowski, Tomasz; Kłodnicka, Monika (Menopause Review/Przegląd Menopauzalny, 2007)
Obesity constitutes one of the most common disorders in the perimenopausal period – it concerns approximately 65% of women in this period of life. Hormone replacement therapy (HRT) does not induce the obesity. The excessive BMI is not an absolute contraindication for HRT; however, hormone therapy should be applied with extreme caution in obese women. The available literature indicates that in peri- and postmenopausal women with indications for the HRT, for safety reasons, the choice of the route of administration and the application of minimally effective dose are crucial.